Downward Rigidity in the Wage for New Hires - Hazell, Jonathon; Taska, Bledi (American Economic Review, 2025)
Wage rigidity is an important explanation for unemployment fluctuations. In benchmark models wages for new hires are key, but there is limited evidence on this margin. We use wages posted on vacancies, with job and establishment information, to measure the wage for new hires. We show that our measure of the wage for new hires is rigid downward and flexible upward, in two steps. First, wages change infrequently at the job level, and fall especially rarely. Second, wages do not respond to rises in unemployment, but respond strongly to falls in unemployment. Job information is crucial for detecting downward rigidity. (JEL E24, E32, J23, J31, J63, M51)